Strategi Pemasaran Produk Griya Bank Syariah Indonesia di Kantor Cabang Pembantu Jelutung Jambi - Alfan Septiardo Ilham; Lucky Enggrani Fitri; Aditya Pratama (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2025)
This study aims to analyze the marketing strategy of the home ownership financing product (Griya) at Bank Syariah Indonesia (BSI), Jelutung Jambi Sub-Branch Office. Griya is one of the leading sharia banking products designed to fulfill the community’s housing needs through Islamic financial principles. However, the relatively low number of Griya customers compared to other products indicates the need for more effective and innovative marketing strategies. This research employs a descriptive qualitative method with a case study approach, supported by a SWOT analysis to identify the strengths, weaknesses, opportunities, and threats in marketing the Griya product. The findings reveal that BSI Jelutung Jambi needs to strengthen market segmentation, enhance promotion through sharia-based education, and optimize digital services to expand its market reach. With adaptive marketing strategies grounded in Islamic values, the Griya product is expected to become more competitive and widely accepted by the public.